2014
DOI: 10.1371/journal.pone.0097183
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Screening Instruments to Predict Posttraumatic Stress Disorder

Abstract: BackgroundFollowing traumatic exposure, a proportion of trauma victims develops posttraumatic stress disorder (PTSD). Early PTSD risk screening requires sensitive instruments to identify everyone at risk for developing PTSD in need of diagnostic follow-up.AimsThis study compares the accuracy of the 4-item SPAN, 10-item Trauma Screening Questionnaire (TSQ) and 22-item Impact of Event Scale-Revised (IES-R) in predicting chronic PTSD at a minimum sensitivity of 80%.MethodInjury patients admitted to a level-I trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 46 publications
1
47
1
2
Order By: Relevance
“…The current study's strength is that we scanned distressed trauma-exposed individuals within 11 days post trauma, thereby providing empirical evidence relevant for considering intranasal OT therapeutically for PTSD prevention in a sample with increased PTSD risk (Mouthaan et al, 2014;Nishi et al, 2010;Walters et al, 2007). Illustrative of our sample's vulnerability for PTSD is the high prevalence of lifetime psychopathology (Ozer et al, 2003): 41% of participants screened positive for at least one lifetime psychiatric disorder and 16% screened positive for prior PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study's strength is that we scanned distressed trauma-exposed individuals within 11 days post trauma, thereby providing empirical evidence relevant for considering intranasal OT therapeutically for PTSD prevention in a sample with increased PTSD risk (Mouthaan et al, 2014;Nishi et al, 2010;Walters et al, 2007). Illustrative of our sample's vulnerability for PTSD is the high prevalence of lifetime psychopathology (Ozer et al, 2003): 41% of participants screened positive for at least one lifetime psychiatric disorder and 16% screened positive for prior PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Acute distress was assessed using the Trauma Screening Questionnaire (TSQ; cutoff score ⩾ 5 (Mouthaan et al, 2014;Walters et al, 2007) and Peritraumatic Distress Inventory (PDI; cutoff score ⩾ 17 (Nishi et al, 2010) (see Frijling et al (2014) for details). Individuals with increased PTSD risk (ie, scoring above TSQ and/or PDI cutoff) were invited to participate.…”
Section: Procedure-screening and Baseline Assessmentmentioning
confidence: 99%
“…Smits, Smit, Cuijpers, & De Graaf, 2007) indicated that sensitivity is more important than specificity. Most screeners for PTSD have at least a sensitivity level of 0.80 (Mouthaan, Sijbrandij, Reitsma, Gersons, & Olff, 2014). Accordingly, we used a sensitivity level of 0.80 as the lower limit to identify early indicators.…”
Section: Methodsmentioning
confidence: 99%
“…Selecting items that are highly related to the outcome yields a set of items that has the strongest possible relation to the outcome in the sample studied, but that set may not be as strongly related to the outcome in a new sample. A few other risk screening tools have been published, but they cannot be used for early predictive screening because they include variables that are typically not available until weeks or months after the event [2125]. None of these screening tools have been given within days of an event and accurately differentiated between those who developed disorder and those who did not [2125].…”
Section: Introductionmentioning
confidence: 99%
“…A few other risk screening tools have been published, but they cannot be used for early predictive screening because they include variables that are typically not available until weeks or months after the event [2125]. None of these screening tools have been given within days of an event and accurately differentiated between those who developed disorder and those who did not [2125]. Screening tools have also been developed to identify those who currently have PTSD, but those are not designed to prospectively predict PTSD at a future time point [26, 27].…”
Section: Introductionmentioning
confidence: 99%